Selective Feeding of a Mixotrophic Dinoflagellate (Lepidodinium sp.) in Response to Experimental Warming and Inorganic Nutrient Imbalance - Liu, Kailin; Ng, Herrick Yin-To; Gao, Zuyuan; Liu, Hongbin (Frontiers in Microbiology, 2022)
Mixotrophic protists are widely observed in the aquatic ecosystems, while how they respond to inorganic nutrient imbalance and ocean warming remains understudied. We conducted a series of experiments on a mixotrophic dinoflagellate Lepidodinium sp. isolated from subtropical coastal waters to investigate the combined effect of temperature and medium nitrate to phosphate ratio (N:P ratio) on the ingestion activities of mixotrophic protists. We found Lepidodinium sp. displayed selective feeding behaviour with a higher ingestion rate on high-N prey (N-rich Rhodomonas salina) when the ambient inorganic N:P ratio was equal to or below the Redfield ratio. The Chesson selectivity index α increased with increasing temperature, suggesting that warming exacerbated the selective feeding of Lepidodinium sp.. Under inorganic nitrogen sufficient conditions (N:P ratio = 64), no selective feeding was observed at 25 and 28 °C, while it occurs at 31 °C, which also indicates that warming alters the feeding behaviour of Lepidodinium sp.. In addition, our results revealed that the total ingestion rate of Lepidodinium sp. under the condition with normal inorganic nutrients (Redfield ratio) was significantly lower than that under nutrient-imbalanced conditions, which indicates that Lepidodinium sp. developed compensatory feeding to balance their cellular stoichiometry and satisfy their growth. Our study is the first attempt on revealing the selective feeding behaviours of mixotrophic protists on prey under different inorganic nutrient environments and rising temperatures, which will contribute to our understanding of the response of marine plankton food web to projected climate changes.